Fate of wild-caught Antechinus flavipes released after physiological experiments - Cooper, Christine; Vernes, K.; Cooper, T. (2009)
Animals may be released into the wild for introduction, translocation or rehabilitation programs. Often, released animals do not survive or reproduce as well as wild conspecifics. Another circumstance whereby animals may be released is the return to the wild of research subjects, and although these animals may be expected to fare better than those from introduction, translocation or rehabilitation programs, there is little information regarding their subsequent survival and reproduction. We examine here the survivorship and reproductive success of five (one male, four female) yellow-footed antechinus (Antechinus flavipes) released back into the wild after being held in captivity for approximately one week for physiological experiments. Three of the four female Antechinus were recaptured after release and, on inspection, all three had 10 pouch young. Survivorship after release of antechinus held in captivity (0.75) was not different from the population as a whole, which ranged between 0.5 and 1.0. We therefore present unequivocal evidence that Antechinus released into the wild after physiological experiments can successfully survive and reproduce. This information is important for wildlife managers and animal ethics committees when considering the fate of ex-research animals.